Social Network and Environment as Determinants of Disability and Quality of Life in Aging: Results From an Italian Study - Guastafierro, Erika; Toppo, Claudia; Corso, Barbara; Romano, Rosa; Campioni, Rino; Brambilla, Ersilia; Facchini, Carla; Bordoni, Sara; Leonardi, Matilde (Frontiers in Medicine, 2022)
Background The increase in life expectancy is leading to a worldwide increase in chronic diseases and disability, with significant concern about their management and long-term care. Investigating the aging process using a bio-psychosocial perspective is essential to understanding how to reduce disability and improve the quality of life of aging people. This study aims to explore the role of social networks and built environment as predictors of disability and quality of life in the Italian population aged over 50 years. Materials and Methods The research protocol is composed of several tools: World Health Organization Disability Assessment Scale 2.0 (WHODAS 2.0), World Health Organization Quality of Life Assessment in Aging (WHOQOL-AGE), Social Network Index (SNI), the Courage Built Environment Self-Reported Questionnaire (CBE-SR), and collection of sociodemographic information and information on health system coverage. Results A total of 431 people were administered the protocol, and among them, 209 were males and 222 were females, with a mean age of 70 years. The majority of the sample reported earning a middle or high school diploma, and 60.6% of the sample declared to have a good health status. The results showed that people with a good social support network have higher levels of functioning and quality of life. However, the built environment did not significantly predict either disability or quality of life. Conclusions These results could provide elements for dialogue with institutions and policymakers. This is fundamental to develop active policies aimed at the implementation of services and systems to promote healthy aging process.